Factors Influencing Nurse Turnover Intentions: A Comprehensive Review of Global Evidence on Organizational, Psychosocial, and Leadership Dimensions - Melisa Anggar Fitiani; Chriswardani Suryawati; Septo Pawelas Arso (Media Keperawatan Indonesia, 2025)
The stability of healthcare around the world is seriously threatened by nurse turnover intention, which is a primary predictor of actual turnover. The necessity to comprehend contributing elements is highlighted by the 47.7% new nurse turnover rate in Korea, which costs over USD 33,733 per nurse. This comprehensive review synthesizes quantitative, qualitative, and mixed-methods evidence to map factors that influence nurse turnover intention across hospital settings. Using a PRISMA-ScR approach, a literature search for "factors of nurse turnover" in Scopus produced 2,274 articles; 13 of these met inclusion criteria and were subjected to thematic analysis. Four primary areas were identified: leadership style (transformational, toxic, bullying), psychosocial aspects (work-life balance, job satisfaction, distress, and social support), and organizational factors (work environment, mentorship). Work-life balance and job satisfaction reduce risk by 30–40%, while a supportive work environment and adequate resources reduce turnover by 10–20%. While toxic or bullying leadership significantly raises turnover intention (β=0.51), transformational leadership enhances retention by 0.082 per unit. There are significant regional differences; for instance, 81.4% of Kenyan nurses plan to quit because their pay is less than $500 USD, which increases the probability of turnover three to five times. The use of cross-sectional research (76.9%) and the lack of worldwide representation are examples of gaps in the literature. To increase retention, holistic approaches that incorporate transformational leadership training, mental health assistance, healthy workplaces, and equitable pay are crucial.